Morphology-controlled nickel oxide nanostructures: unlocking high-performance supercapacitor applications - Govindhasamy Murugadoss; Narthana Kandhasamy; Irina V. Zaporotskova; Nachimuthu Venkatesh; Sunitha Salla; Sakthivel Pandurengan (Chemical Physics Impact)
Nickel oxide (NiO) has garnered significant attention as a high-performance electrode material for energy storage devices due to its excellent electrochemical activity and high theoretical capacity. In this study, well crystalline cubic structure NiO with diverse morphologies-three-dimensional spherical (NiO-3D-S), two-dimensional sheet-like structure (NiO-2D), and three-dimensional asymmetric structure (NiO-3D-A) were synthesized via a simple hydrothermal method. The surface morphology was effectively tailored using polyvinylpyrrolidone (PVP) in combination with various surfactants, including ethylene glycol (EG), cetyltrimethylammonium bromide (CTAB), and glycerol. Among the synthesized structures, the 2D sheet-like porous NiO (NiO-2D) exhibited superior electrochemical performance, achieving a high specific capacitance of 853.17 F g⁻¹ at a current density of 1 mA g⁻¹. It also demonstrated excellent cycling stability, retaining approximately 92 % of its initial capacitance after 3000 charge–discharge cycles. This enhanced performance is attributed to its unique porous architecture composed of ultra-fine grains self-assembled into uniform 2D sheets, which facilitate rapid ion diffusion and efficient charge transport. To evaluate practical applicability, an asymmetric two-electrode device was fabricated using NiO-2D as the positive electrode. The device delivered an energy density of 3.2 Wh kg⁻¹ and a power density of 360 W kg⁻¹, and successfully powered a red light-emitting diode (LED), demonstrating its potential for real-world applications. These findings underscore the promise of 2D sheet-like porous NiO as an advanced electrode material for high-performance and durable electrochemical energy storage systems.